Extreme Relativistic Electron Fluxes in GPS Orbit: Analysis of NS41 BDD‐IIR Data - Nigel P. Meredith; Thomas E. Cayton; Michael D. Cayton; Richard B. Horne (Space Weather)
Abstract Relativistic electrons in the Earth's outer radiation belt are a significant space weather hazard. Satellites in GPS‐type orbits pass through the heart of the outer radiation belt where they may be exposed to large fluxes of relativistic electrons. In this study we conduct an extreme value analysis of the daily average relativistic electron flux in Global Positioning System orbit as a function of energy and L using data from the US NS41 satellite from 10 December 2000 to 25 July 2020. The 1 in 10 year flux at L = 4.5, in the heart of the outer radiation belt, decreases with increasing energy ranging from 8.2 × 106 cm−2s−1sr−1 MeV−1 at E = 0.6 MeV to 33 cm−2s−1sr−1 MeV−1 at E = 8.0 MeV. The 1 in 100 year is a factor of 1.1–1.7 larger than the corresponding 1 in 10 year event. The 1 in 10 year flux at L = 6.5, on field lines which map to the vicinity of geostationary orbit, decrease with increasing energy ranging from 6.2 × 105 cm−2s−1sr−1 MeV−1 at E = 0.6 MeV to 0.48 cm−2s−1sr−1 MeV−1 at E = 8.0 MeV. Here, the 1 in 100 year event is a factor of 1.1–13 times larger than the corresponding 1 in 10 year event, with the value of the factor increasing with increasing energy. Our analysis suggests that the fluxes of relativistic electrons with energies in the range 0.6 ≤ E ≤ 2.0 MeV in the region 4.25 ≤ L ≤ 4.75 have an upper bound. In contrast, further out and at higher energies the fluxes of relativistic electrons are largely unbounded.